Temporomandibular joint impairment in a patient with juvenile idiopathic arthritis: case report (Research, Society and Development, 2022)
Objective: This article aims to present a case report of a patient with Juvenile Idiopathic Arthritis (JIA), with orofacial sequelae and impairment of the temporomandibular joint (TMJ). Case report: Patient HMM, 26 years old, female, Caucasian, attended the Occlusion, Temporomandibular Disorders, and Orofacial Pain Clinic service at UFPB with a complaint of facial pain and limited mouth opening. She reported having JIA, limited mouth opening for more than 2 months, joint sounds, using muscle relaxants, and a history of intensive use of NSAID selective COX-2 inhibitor. The extraoral examination revealed opening limitation (22 mm), with deflection to the right side, without symptoms for muscle palpation and TMJ auscultation, but with lateral sensitivity on the right side during TMJ palpation. There was an alteration in the occlusion in the position of maximum habitual intercuspation, with mild occlusal instability. The patient underwent TMJ tomography and serological tests and, after clinical and laboratory evaluation, the suggestive diagnosis was JIA with involvement of the Right TMJ and possible displacement of the articular disc without reduction in the same TMJ. The treatment consisted of counseling, associated with Occlusal Plaque, physiotherapy of compresses and stretching and rheumatological follow-up. After 6 months, there was a significant improvement in mouth opening (22 mm to 33 mm), with moderate pain control. Conclusion: The evaluation of patients should encompass a comprehensive and systemic view, with diagnosis and treatment performed in a multidisciplinary way, enabling their quality of life.